As configurações do amor nas pastorelas galego-portuguesas - Apolinário, Marciléia de Souza (2010)
The objective of this paper is to present a reading of the conception of Love that is formed in Galleco-portuguese pastourelles. The basis for this reading is the analysis of medieval society characteristics, which assertively influenced the religious spirit of the troubadour lyricism. The dissertation is developed from the recuperation of the Portuguese social/cultural contexts of the 12th and 13th centuries, for a better understanding of the chosen lyrics. For that matter, the stylistical and rhetorical resources used by the troubadours in the literary writing of rural theme have been observed. Because it concerns lyrical poetry of pastoral nature, the verifying of the lyrical poetry concepts and references related to Love during different philosophical and literary history periods has been chosen in order to assure a better comprehension of the relationship between Men and Love in this culturally relevant period called the Middle Age. The body of this paper consists of eight texts considered to be pastourelles selected from the Crestomatia Arcaica, published by Nunes (1947). The medieval studies such as Duby (1988), Franco Jr. (1990), and the critical studies of Cavalcanti (2005) and Brea (2006), among others, were the historical/ theorical basis for this subject.